The modern forms of witchcraft in Zambia: an analysis of local witchcraft narratives in urban settings of Lusaka - Mildnerová, Kateřina (Religio, 2016)
This article, based on data gathered during long-term ethnographic fieldwork, deals with modern forms of witchcraft in Lusaka, Zambia. The interpretation of witchcraft narratives grounded in analyses of multi-episodic medical cases builds on the theoretical assumptions of scholars studying contemporary forms of witchcraft in connection with the crises of modernity, ongoing globalisation, capitalism, and the process of the socio-political and economic transformations of modern African societies. This article does not tackle witchcraft in Lusaka only in the narrow sense as the aetiology of an individual illness, but on a more general level as a specific kind of worldview, a local discourse explaining the presence of evil, misfortune, and inequalities in the world. The article attempts to answer the question of what kind of socio-economic problems the imagery of current urban witchcraft in Lusaka reflects, and how the local witchcraft discourse is socially and culturally constructed in specific situations and events.